Termite environmental tolerances are more linked to desiccation than temperature in modified tropical forests - Woon,JS; Boyle,MJW; Ewers,RM; Chung,A; Eggleton,P (Insectes Sociaux, 2019)
Termites are vital members of old-growth tropical forests, being perhaps the main decomposers of dead plant material at all stages of humification (decay). Termite abundance and diversity drop in selectively logged forest, and it has been hypothesised that this drop is due to a low tolerance to changing micro-climatic conditions. Specifically, the thermal adaptation hypothesis suggests that tropical species are operating at, or close to, their thermal optimum, and therefore, small temperature increases can have drastic effects on abundance, however, other climatic variables such as humidity might also cause termite abundance to drop. We tested termite tolerance to these two climatic variables (temperature and humidity). We found that termites had a higher CTmax than expected, and that three traits, feeding group, body sclerotisation, and nesting type, were significantly correlated with CTmax. We found that termite desiccation tolerance was low, however, and that all termite genera lost significantly more water in a desiccated environment than in a control. Body sclerotisation, the only trait that was tested, was surprisingly not significantly correlated with desiccation tolerance. Our results suggest that desiccation, rather than ambient temperature, may be the determining factor in dictating termite distributions in modified forests. Should climate change lead to reduced humidity within tropical rainforests, termite abundances and the rates of the functions they perform could be severely reduced.